2011
DOI: 10.1016/j.jnci.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic factors of diffuse large B cell non-Hodgkin lymphoma: A retrospective study

Abstract: DI of Cyclophosphamide and Doxorubicin is important in the future treatment regimen plan for DLBCL especially in high risk cases. In addition to aa-IPI and its elements, extra nodal sites and bulk of the tumor proved to be significant predictors and prognostic factors for DLBCL treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
5
16
1
3
Order By: Relevance
“…Pertinent clinical data, including age, gender, initial presenting symptoms, laboratory examination findings, pathologic diagnosis, involved organs, International Prognostic Index (IPI) score (11,12), detailed treatment modalities, time to death and the date of the last follow-up, were collected for the analysis. Additional workup examinations included bone marrow biopsies, plain X-ray films of the bone, computed tomography (CT), magnetic resonance imaging (MRI) of the bone lesion(s) and positron-emission tomography (PET).…”
Section: Patientsmentioning
confidence: 99%
“…Pertinent clinical data, including age, gender, initial presenting symptoms, laboratory examination findings, pathologic diagnosis, involved organs, International Prognostic Index (IPI) score (11,12), detailed treatment modalities, time to death and the date of the last follow-up, were collected for the analysis. Additional workup examinations included bone marrow biopsies, plain X-ray films of the bone, computed tomography (CT), magnetic resonance imaging (MRI) of the bone lesion(s) and positron-emission tomography (PET).…”
Section: Patientsmentioning
confidence: 99%
“…[13] It seems that demonstration of bcl-12 expression should always raise suspicion of a systemic lymphoma involving the skin secondarily and unfavorable course of disease. [2,7] However, as seen in the present case, the disease ran an indolent course with no intracranial invasion despite of bcl-12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indolent lymphomas progress slowly and have long-term survival; while aggressive lymphomas may have poor prognosis that progress in a short time [1]. International prognostic index (IPI) is still known as the effective prognostic factor for aggressive lymphomas today [3], [6]. But more and more researchers have focused on the effect of inflammation and immune-related gene polymorphisms on pathogenesis and prognosis of NHL.…”
Section: Discussionmentioning
confidence: 99%
“…But a number of patients do not achieve complete remission or relapse after chemotherapy. Several studies have shown that the courses of NHLs are variable, and NHL survival patterns vary by subtypes, suggesting different prognostic risk factors for NHL histological subtypes [3], [4], [5]. International prognostic index (IPI) model was developed for predicting outcome in patients with aggressive NHL in 1993, which pointed out that more than 60-year-old, advanced tumor stage, poor performance score, extranodal involvement and elevated lactate dehydrogenase (LDH) were adverse prognostic factors for NHL [6].…”
Section: Introductionmentioning
confidence: 99%